2018
DOI: 10.1051/matecconf/201822503016
|View full text |Cite
|
Sign up to set email alerts
|

Chassis dynamometer for electric two wheelers

Abstract: In recent years, electric two-wheelers are emerging as one of the alternatives to improve the sustainability of transportation energy and air quality, especially in urban areas. Although electric two-wheeler motorcycles are environmentally friendly, they underperform compared with gasoline two-wheelers in many respects, particularly in speed and cruise distance between refuelling and recharging. Therefore, the engine development program can be done with a dynamometer. Variables such as the shape of torque and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Through an experiment, it is shown that calculated and measured results exhibit a good correlation. In order to evaluate the performance of electric bicycles experimentally, Hassan [12] designed a chassis dynamometer that can measure mechanical power, torque, and speed, with an applied road-load. The designed chassis dynamometer can effectively measure the transmission efficiency of electric bicycles.…”
Section: Introductionmentioning
confidence: 99%
“…Through an experiment, it is shown that calculated and measured results exhibit a good correlation. In order to evaluate the performance of electric bicycles experimentally, Hassan [12] designed a chassis dynamometer that can measure mechanical power, torque, and speed, with an applied road-load. The designed chassis dynamometer can effectively measure the transmission efficiency of electric bicycles.…”
Section: Introductionmentioning
confidence: 99%